Stimulant ADHD medication and risk for substance abuse - Chang, Zheng (2013)
BACKGROUND: There are persistent concerns of long-term effects of stimulant ADHD medication on the development of substance abuse. METHODS: Using Swedish national registers, we studied all individuals born 1960–1998 and diagnosed with ADHD (26,249 men and 12,504 women). We investigated the association between stimulant ADHD medication in 2006 and substance abuse during 2009. Substance abuse was indexed by substance-related death, crime, or hospital visits. RESULTS: ADHD medication was not associated with increased rate of substance abuse. Actually, the rate during 2009 was 31% lower among those prescribed ADHD medication in 2006, even after controlling for medication in 2009 and other covariates (hazard ratio: 0.69; 95% confidence interval: 0.57–0.84). Also the longer duration of medication, the lower the rate of substance abuse. Similar risk reductions were suggested among children and when investigating the association between stimulant ADHD medication and concomitant short-term abuse. CONCLUSIONS: We found no indication of increased risks of substance abuse among individuals prescribed stimulant ADHD medication; if anything, the data suggested a long-term protective effect on substance abuse. Although stimulant ADHD medication does not seem to increase the risk for substance abuse, clinicians should remain alert to the potential problem of stimulant misuse and diversion in ADHD patients.